Metamorphosis From Music To Politics: Study On Celebrity Giring Ganesha In Indonesian Legislative Election - Achmad Jamil; Rizki Briandana; Rustono Farady Marta; Fahmi Fotaleno; Muhammad Raqib Mohd Sofian (Communication Science Department. UIN Sunan Kalijaga Yogyakarta, 2024)
Vol.15/No.1 APRIL 2022 - Profetik Jurnal Komunikasi Page (5-17)